PENGARUH MEDIA PEMBELAJARAN KIPAS ( KINCIR ANGIN PANEL SURYA) TERHADAP HASIL BELAJAR SISWA PADA TEMA 2 SELALU BERHEMAT ENERGI PEMBELAJARAN 1 PELAJARAN IPA KELAS IV SD NEGERI 091288 SIBAGANDING - Maya Kristina Parhusip; Rio Parsaoran Napitupulu; Ady Frenly Manullang (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research aims to determine the effect of fan learning media (solar panel windmills) on the learning outcomes of class IV students Theme 2 Always save energy in learning 1 science lesson class IV SD Negeri 091288 Sibaganding. This type of research is quantitative research using the Quasy method Experimental Design. The form of Quasy Experiment Design used in this research is One Group Pretest – Posttest Design. The sample for this research was 18 class IV students. The sampling technique in this research is a simple random sampling technique. Data collection in this research used pretest and posttest. The pretest is carried out to determine students' initial abilities and the posttest is carried out to determine student learning outcomes. The test is in the form of objective test questions (multiple choice) which have four choices, namely a.b,c, and d, totaling 20 questions. Based on the Hypothesis Test Results with a significance of 0.00 < 0.5, it can be concluded that there is an Influence of Fan Learning Media (Windmills). Solar Panels) on the Learning Outcomes of Class IV Telma 2 Students Always Save Energy Class IV Science Learning lessons at SD Negeri 091288 Sibaganding. Based on the results of the hypothesis test, h_0〖 is rejected h〗_a is accepted which shows that there is an influence of the fan learning media (panel windmills surya) on student learning outcomes.